The Relationship Between Logical Thinking And The Semester Achievement Index Of Students Of Penjas Pgri Jombang University - Satya Hasmara, Puguh; Nurhasan, Nurhasan; Suroto, Suroto; Ma’arif, Ilmul (International Journal of Educational Research & Social Sciences, 2023)
Logical thinking can show a mature attitude to help choose to solve problems provided by educators for students. Because logical thinking solves problems intelligently, swiftly, deftly, confidently, and skillfully. Logical thinking can help students' academic and non-academic achievements. This study aims to determine the relationship between logical thinking and the semester achievement index of PGRI Jombang University students. In this study, researchers only want to know the relationship between variable X and variable Y, how to distribute questionnaires to respondents. Data collection techniques take data with questionnaires and documentation. The data analysis technique uses a normality test with the results of logical thinking scores of 0.883 > 0.05 and Semester Achievement Index of 0.001 < 0.05. It can be concluded that the logical thinking variable is normally distributed while the semester achievement index variable is not normally distributed, a linear test with b resultsbased on the analysis obtained F calculate 0.970 with a signification level of 0.539. This proves that F count 0.970 < F table 3.9 1. Because the calculated F value is smaller than the F table, it can be concluded that there is a significant linear relationship between the logical thinking variable (X) and the semester achievement index variable (Y), and the correlation test with the results Based on the test results shows a correlation value of -0.055. This indicates that there is no relationship between logical thinking and student semester achievement index.Based on the results of research on the relationship of logical thinking to the semester achievement index of Physical Education Students at PGRI Jombang University by looking at the results of data analysis indicates that there is no relationship between logical thinking and the semester achievement index of high, medium, and low ability students.